THE EFFECT OF 25% BAY LEAF EXTRACT AND 75% SMALL WHITE GINGER EXTRACT IMMERSION IN THE COLOR CHANGE OF ACRYLIC BASE - Nadia Rizky Safitri; Debby Saputera; Isnur Hatta (FKG Unlam, 2019)
Background: The most widely used denture is made from heat cured acrylic type. Acrylic resin has some disadvantages, one of which is easy to absorb liquid like water or chemical that affect color change. Alkaline peroxide is a denture cleanser that mostly sold on the market. A mixture of 25% bay leaf and 70% small white ginger extract can be used as natural denture cleanser. Objective: This study aimed to know the color change of heat cured resin base that immersed in a mixture of 25% bay leaf and 70% small white ginger extract. Method: This study was true experimental study with pretest and posttest with control group design, using simple random sampling. The sample was round with a diameter of 15mm and thickness 2mm. The samples were 18 heat cured acrylic resins which were divided into 3 groups, the mixture of 25% bay leaf and 70% small white ginger extract, alkaline peroxide, and aquades. The color change of the sample was tested using digital analysis tools set. Results: The mean value of color change of heat cured acrylic resin base after immersion in a group of mixed extracts, alkaline peroxide, and aquades were (5.22), (3.45) and (2.46). Data were analyzed using the One Way ANOVA parametric test and Bonferroni Post Hoc test. Conclusion: There is a difference in color change on the heat cured resin after immersion in a mixture of extract and alkaline peroxide. The value of acrylic resin that immeresed in mixed extract has the higher color change.